Effectiveness of solution-focused brief counseling to increase achievement motivation of bullying victims - Wiyono, Bambang Dibyo; Nuryono, Wiryo; Ghozali, Muhamad Afifuddin; Adebowale, Olusegun Fatai; Kamal, Akmal Nasri; Putri, Aulia Ramadhani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The phenomenon of bullying has been a problem in almost every school, and many factors have been attributed to someone becoming a victim of bullying. The intimidation that occurs to victims of bullying has a negative impact on many facet of their live, one of which is a decrease in academic achievement due to lack of motivation. Achievement motivation is required by every student to accomplish academic tasks and achieve set goals, especially victims of bullying who have low achievement motivation. This study aims to test the effectiveness of the Solution-Focused Brief Counseling approach to increase the achievement motivation of students who are victims of bullying at SMP Negeri 35 Surabaya. This study uses a quantitative approach adopting pre-test post-test control group research design. The research participants comprised 6 students of class VIII of SMP Negeri 35 Surabaya who were selected using simple random sampling technique which were then divided into 2 groups, namely the experimental group and the control group. Data collection was carried out using a scale instrument for bullying victims and achievement motivation which had been tested for validity and reliability. This study consisted of 3 treatment meeting sessions and 2 test sessions, namely pre-test and post-test. Data were analyzed using the Mann-Whitney test. The results showed a significant increase in achievement motivation of bullying victims in the experimental group compared to the control group (0.046 < 0.05). So it can be concluded that individual counseling with the Solution-Focused Brief Counseling approach has proven effective in increasing the achievement motivation of bullying victims. Solution-focused brief counseling can be an option for school counselors to increase the achievement motivation of students who are victims of bullying.